2014
DOI: 10.1038/nm.3449
|View full text |Cite
|
Sign up to set email alerts
|

RIPK3 as a potential therapeutic target for Gaucher's disease

Abstract: Gaucher's disease (GD), an inherited metabolic disorder caused by mutations in the glucocerebrosidase gene (GBA), is the most common lysosomal storage disease. Heterozygous mutations in GBA are a major risk factor for Parkinson's disease. GD is divided into three clinical subtypes based on the absence (type 1) or presence (types 2 and 3) of neurological signs. Type 1 GD was the first lysosomal storage disease (LSD) for which enzyme therapy became available, and although infusions of recombinant glucocerebrosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
133
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(144 citation statements)
references
References 49 publications
9
133
1
1
Order By: Relevance
“…38 Altogether, these findings suggest opportunities for RIPK3 inhibitors in the treatment of diseases where high RIPK3 kinase activity promotes human pathologies, also including steatohepatitis 36 and Gaucher's disease. 39 Materials and Methods Cell lines. Primary MEFs were generated by mating animals of the required genotypes and harvesting embryos at E12-E14 based on palpation.…”
Section: Discussionmentioning
confidence: 99%
“…38 Altogether, these findings suggest opportunities for RIPK3 inhibitors in the treatment of diseases where high RIPK3 kinase activity promotes human pathologies, also including steatohepatitis 36 and Gaucher's disease. 39 Materials and Methods Cell lines. Primary MEFs were generated by mating animals of the required genotypes and harvesting embryos at E12-E14 based on palpation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in recent years have demonstrated the involvement of necroptosis in a number of pathophysiological processes, such as atherosclerosis (6), skin inflammation (7)(8)(9), chronic intestinal inflammation (10, 11), Gaucher's disease (12), acute liver injury (13,14), and heightened intestinal inflammation (15).…”
mentioning
confidence: 99%
“…RIP3 knockout can significantly ameliorate the development of disease and prolong the survival of animals. [38] Amyotrophic lateral sclerosis (ALS) is the most adult onset motor neuron degenerative disease, in which inflammation is the most striking hallmark of pathological changes. Recently, it has been demonstrated that in the spinal cord of the ALS model, motor neurons also undergo necroptosis.…”
Section: Necroptosis and Neurological Diseasesmentioning
confidence: 99%